2009
DOI: 10.1007/s00586-009-1183-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of free-hand placement of thoracic pedicle screws in adolescent idiopathic scoliosis: how much of a difference does surgeon experience make?

Abstract: The use of thoracic pedicle screws for the treatment of adolescent idiopathic scoliosis (AIS) has gained widespread popularity. However, the placement of pedicle screws in the deformed spine poses unique challenges, and surgeons experience a learning curve. The in vivo accuracy as determined by computed tomography (CT) of placement of thoracic pedicle screws in the deformed spine as a function of surgeon experience is unknown. We undertook a retrospective review to determine the effect of surgeon experience on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 32 publications
3
74
3
5
Order By: Relevance
“…As Marc Nuwer and colleagues wrote almost 2 decades ago about how neuromonitoring reduced neurological deficits after scoliosis surgery: "... the best and most cost effective way to treat paraplegia is by preventing it in the first place." 42 Finally, and like numerous other authors, 3,20,23,49,50,59,62 we have adopted a medial breach alarm level of 2 mm or more as a clinically relevant breach magnitude, a degree of encroachment that should be avoided whenever possible.…”
Section: Discussionmentioning
confidence: 91%
“…As Marc Nuwer and colleagues wrote almost 2 decades ago about how neuromonitoring reduced neurological deficits after scoliosis surgery: "... the best and most cost effective way to treat paraplegia is by preventing it in the first place." 42 Finally, and like numerous other authors, 3,20,23,49,50,59,62 we have adopted a medial breach alarm level of 2 mm or more as a clinically relevant breach magnitude, a degree of encroachment that should be avoided whenever possible.…”
Section: Discussionmentioning
confidence: 91%
“…However, these results were not comprehensive due to a lack of reports from small medical centers and newer surgeons. The breach rates are related with the years of experience of the surgeon; overall breaches and medial breaches are 12.9% and 8.0%, respectively, for surgeons with less than five years of experience, and they are 10.8% and 3.5% [17], respectively, for surgeons with more than five years of experience [17]. These results illustrate that the medial breach rate was significantly lower for the experienced surgeons.…”
Section: Introductionmentioning
confidence: 70%
“…It has been well documented that there is a learning curve associated with the insertion of thoracic pedicle screws. 7,9,16 As Joglekar et al concluded, "There are no shortcuts." 9 In other words, an inexperienced surgeon, as compared with an experienced one, is going to have an increased breach rate.…”
Section: Discussionmentioning
confidence: 99%